2016
DOI: 10.1016/j.devcel.2015.12.029
|View full text |Cite
|
Sign up to set email alerts
|

The 1p36 Tumor Suppressor KIF 1Bβ Is Required for Calcineurin Activation, Controlling Mitochondrial Fission and Apoptosis

Abstract: KIF1Bβ is a candidate 1p36 tumor suppressor that regulates apoptosis in the developing sympathetic nervous system. We found that KIF1Bβ activates the Ca(2+)-dependent phosphatase calcineurin (CN) by stabilizing the CN-calmodulin complex, relieving enzymatic autoinhibition and enabling CN substrate recognition. CN is the key mediator of cellular responses to Ca(2+) signals and its deregulation is implicated in cancer, cardiac, neurodegenerative, and immune disease. We show that KIF1Bβ affects mitochondrial dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…Conditional KIF1Bβ Knock-out (KO) mouse was generated by Dr. Susanne Schlisio's laboratory as described previously [21]. Briefly, the constitutive KO alleles specific for KIF1Bβ-isoform were obtained by crossing transgenic mice expressing Dopamine β-hydroxylase-Cre recombinase (DBH-Cre) with mice expressing floxed-targeting construct, which will result in the deletion of exon 22 and the subsequent loss of KIF1Bβ-isoform function [22].…”
Section: Methodsmentioning
confidence: 99%
“…Conditional KIF1Bβ Knock-out (KO) mouse was generated by Dr. Susanne Schlisio's laboratory as described previously [21]. Briefly, the constitutive KO alleles specific for KIF1Bβ-isoform were obtained by crossing transgenic mice expressing Dopamine β-hydroxylase-Cre recombinase (DBH-Cre) with mice expressing floxed-targeting construct, which will result in the deletion of exon 22 and the subsequent loss of KIF1Bβ-isoform function [22].…”
Section: Methodsmentioning
confidence: 99%
“…Dynamin-Related Protein 1 (DRP1) is an upstream regulator of mitochondrial fission [13]. Several studies demonstrated that targeting DRP1 and mitochondrial fission may be an effective approach in cancer treatment [14]. Additionally, Fission, Mitochondrial 1 (FIS1), which serves as a receptor to recruit DRP1 to mitochondria, has also been uncovered to promote CDDP sensitivity in tongue squamous cell carcinoma [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Developmental Cell , Li et al (2016) show that KIF1Bβ binding releases calcineurin autoinhibition, leading to dephosphorylation of the DRP1 GTPase and subsequent mitochondrial fragmentation. KIF1Bβ impairment causes mitochondrial hyperfusion, impairing developmental apoptosis and promoting tumorigenesis.…”
mentioning
confidence: 95%
“…In this issue of Developmental Cell , Li et al (2016) provide an additional mechanism to explain the effects of KIF1Bβ on tumorigenesis. These authors found that KIF1Bβ activates the Ca 2+ -calmodulin-dependent protein phosphatase calcineurin by binding and stabilizing the calmodulin-calcineurin complex, relieving enzymatic autoinhibition (more completely than Ca 2+ alone) and permitting substrate recognition broadly.…”
mentioning
confidence: 99%
See 1 more Smart Citation